Køn, krop og ånd i middelalderen - Wiberg Pedersen, Else Marie (Kvinder, Køn & Forskning, 1997)
Very often, the medieval view on "gender" and "body" is depicted either unequivocally negative or just equivocal. According to this simplistic picture, a number of medieval men and women have been portrayed as alternately extremely misogynist and extremely submissive and self-suppressing. With the examples of Bernard of Clairvaux, Beatrice of Nazareth, Mechtild of Hackeborn, and Gertrud of Helfta, this article tries to differentiate more subtly the perception of the concepts "woman/female" and "man/male" by pointing to their function as symbols within the Christian tradition. Furthermore, it is demonstrated that the view on body/soul is not an expression of simple dualism.